Stress and vowel reduction by Korean learners of English - Park, Ha Lim, author; Delahunty, Gerald, advisor; Marques, Luciana, advisor; Knarvik, Nyssa, committee member (Colorado State University. Libraries, 2021)
With regard to teaching a second language, it has been controversial what a language teacher should focus on in developing intelligibility versus native-like production. Having a foreign accent is unavoidable for late second or foreign language learners because it becomes harder to acquire and produce the native-like pronunciation in a second language, essentially because older learners already have a well-established first language, which mediates the acquisition of a second language. A consequence of this mediation is negative transfer from the L1 to L2, which occurs because of phonological system differences between the L1 and L2, influencing language learners on their production of segmental and suprasegmental aspects of pronunciation. The purpose of this thesis is to examine patterns of vowel reduction in Korean accented English, with the goal of finding pronunciation issues in the English for Korean learners that might be due to transfer effects from an acoustic-phonetic standpoint. In terms of methodology, a corpus linguistics approach is used since the corpus approach enables access to a sufficient amount of digitized recordings of the participants easily and economically. Scripted recorded speech samples from native English and Korean speakers of the Wildcat Corpus which was shared by Ann Bradlow from Northwestern University (Bradlow, n.d.) were used for data analysis. The data analysis will be divided into two parts. One is focused on the duration ratios of the unstressed vowels produced by Korean and English speakers, and the other is focused on the formant values of the unstressed vowels. Results showed that the duration ratios of the unstressed vowels produced by Korean speakers were bigger than native English speakers, indicating that Korean speakers do not reduce the unstressed vowels as English speakers do. Also, there were discrepancies in the qualities of the unstressed vowels between native Korean and English speakers although the formant values were very similar. Korean speakers tend to assimilate English unstressed vowels into similar vowels in their vowel inventory and produce them as full vowels. Therefore, vowel reduction does not occur by Korean speakers of English in the same way as native English speakers do, consequently it causes Korean accented English. Based on the literature review related to the hypotheses and the findings of the current study, pedagogical suggestions will be provided regarding suprasegmental instruction that might help Korean learners of English to be aware of spoken English stress patterns focusing on vowel production that strongly relates to the intonation in English.
Keywords: Korean; negative transfer; vowel reduction; Korean learners of English; foreign accent; phonology